Gemstone settings : the jewelry maker's guide to styles & techniques - Young, Anastasia (Interweave, 2012)
"Gemstone Settings features an extensive summary of stone-setting and techniques for creating beautiful gemstone jewelry, from basic bezels and prongs to pave;, carre;, clusters, and numerous others-including cold joins, precious metal clay, settings for fragile stones, and settings that allow the stones to move. You'll also discover detailed information about stones and metals-including their suitability, photos and illustrations for visual support, what makes a design wearable and durable, and detailed information on pre-made versus handmade settings."--